FORMATION AND PROGRESS OF THE SURKHANDARYODA ARTS THEATER - N. Azima Hayrullayevna Nasriddinova (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, some features of the formation and development of theater art in Surkhandarya are analyzed based on reliable sources.